ISOLASI DAN KARAKTERISASI PLANT GROWTH PROMOTING RHIZOBACTERIA DARI RIZOSFER KEBUN KARET RAKYAT - Nova Wulandari; Mokhamad Irfan; Robbana Saragih (UIR Press, 2019)
ABSTRACT The diversity of vegetation that grows on the ground will affect the number and type of microbes in the rhizosphere of folk rubber plantations. The purpose of this research is to know the population, genus, and biological activity of PGPR bacteria (IAA hormone producers, phosphate solvents and biocontrol agents) originating from the rhizosphere of folk rubber plantations. This research was conducted from March to May 2018 at the Laboratory of Pathology, Entomology and Microbiology Faculty of Agriculture and Animal Sciences, Islamic State University Sultan Syarif Kasim Riau and UPT Health and Environment Laboratory. This research used an observation method by taking soil samples that are composted, and data are presented in descriptive form. The parameters observed in this research were soil pH, bacterial population, characterization of PGPR bacteria includes macroscopic, microscopic, biochemical reaction test and PGPR bacterial biological activity (IAA test qualitatively, phosphate solvent test and in-vitro inhibitory test). The results showed that the pH of the soil obtained at a depth of 0-20 cm was 3.19 with a bacterial population of 1.06 × 106 CFU/g of soil. A total of 4 isolates were able to produce IAA hormones namely genus Bacillus sp.1, Bacillus sp.2, Bacillus sp.3, and Bacillus sp.5. A total of 2 isolates were able to dissolve foster, namely genus Bacillus sp.1 and Bacillus sp.2 and 2 isolates were able to play a role as inhibitory power against Fusarium sp. namely the genus Bacillus sp. 4 and Bacillus sp.5. There were 5 isolates of PGPR bacteria that had different biological activity abilities, namely genus Bacillus sp.1, Bacillus sp.2, Bacillus sp.3, Bacillus sp.4, and Bacillus sp.5.